2022
DOI: 10.1021/acsomega.2c04286
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N-Methyltransferase Remodeled Cell Metabolism and Aggravated Proinflammatory Responses by Activating STAT3/IL1β/PGE2 Pathway

Abstract: Nicotinamide N-methyltransferase (NNMT) is a cytosolic methyltransferase, catalyzing N-methylation of nicotinamide (NAM) to form 1-methylnicotinamide (1-MNAM), in which S-adenosyl-l-methionine (SAM) is the methyl donor. It has been well documented that NNMT is elevated in multiple cancers and promotes tumor aggressiveness. In the present study, we investigated the effects of NNMT overexpression on cellular metabolism and proinflammatory responses. We found that NNMT overexpression reduced NAD+ and SAM levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Some reports have linked Nnmt and IL18 with cancer progression through the STAT3/IL1β pathway [42]. Our microarray analysis showed that the expression of Nnmt is significantly decreased in Il18 −/− mice.…”
Section: Cancer-related Genes In Il18mentioning
confidence: 53%
“…Some reports have linked Nnmt and IL18 with cancer progression through the STAT3/IL1β pathway [42]. Our microarray analysis showed that the expression of Nnmt is significantly decreased in Il18 −/− mice.…”
Section: Cancer-related Genes In Il18mentioning
confidence: 53%
“…With regard to EMT transcription factors (EMT‐TFs), an overall and consistent reduction in the level of ZEB1, ZEB2, TWIST1 and (to a minimal extent) SLUG was observed with SP treatment in the 72 h time course, while SNAIL was found up‐regulated, indicating the potential supporting role of EMT‐TFs inhibition to EMT reversal (Appendix Fig S2D). The EMT inhibition by SP was further validated by additional EMT‐specific marker, NNMT (Shaul et al , 2014; Yang et al , 2022) (Appendix Fig S2E). Finally, mass spectrometry analysis of A549 cells treated with SP confirmed a significant increase in the intracellular propionate level (~27 folds) indicating the cellular uptake of exogenously supplemented propionate (Fig EV1H).…”
Section: Resultsmentioning
confidence: 95%
“…1-Methylnicotinamide is a direct metabolite of niacin and has various immune-regulatory properties, and it can inhibit the activation of the NLRP3 inflammasome by regulating reactive oxygen species levels [ 46 ]. Moreover, niacin is catalyzed by nicotinamide N-methyltransferase to generate 1-Methylnicotinamide, and overexpression of nicotinamide N-methyltransferase can activate the STAT3/IL1β/PGE2 pathway, leading to worsened inflammatory reactions [ 47 ]. Compared to the model group rats, there was a significant decrease in 1-Methylnicotinamide in the uteri of the graphene nuangong acupoint plaster group rats.…”
Section: Discussionmentioning
confidence: 99%